Democratizing Energy, Energizing Democracy: Central Dimensions Surfacing in the Debate - Sorman, Alevgül H.; Turhan, Ethemcan; Rosas-Casals, Marti (Frontiers in Energy Research, 2020)
This perspective piece sets to contribute to the academic and practitioner debates around energy democracy in the age of climate crisis. In tackling the present-day energy transition challenges in a democratic, equitable, just and sustainable manner, we argue that sound research shall take alternative currents to centralized access to and control of energy decision making at its core as well as exploring new and novel ways to deal with production and distribution issues. Critical research on new actors, materialities, values, worldviews, democracy, and justice on energy is well-situated to meet these challenges. Navigating value systems, exploring enabling or disabling material qualities, focusing on ruptures, continuities, and emerging new geographies all carry a promise in critical energy research. We contend that ‘normative, political and embodied’ research strategies must be used to defeat the far right’s the particularly mischievous approach to planetary futures.